2004
DOI: 10.1111/j.0001-6349.2004.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of spontaneously occurring postmenopausal bleeding in the general population

Abstract: This study indicates that recurrence of bleeding is very common in the time immediately after the 12 months of amenorrhea after what is currently defined as the final menstrual period, declining to low frequencies more than 3 years after the final menstrual period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 10 publications
1
36
0
2
Order By: Relevance
“…Postmenopausal bleeding occurs with a 10.7% frequency in the general population, 61 is associated with a 4.4% prevalence of endometrial malignancy, 62 and may be an independent predictor of significant endometrial pathology. 59 Although it seems intuitive that the frequency of NECs would be significantly higher in patients presenting with bleeding than in their asymptomatic counterparts, published studies have reported conflicting results on this point (Table 7).…”
Section: Significance Of Associated Symptomsmentioning
confidence: 99%
“…Postmenopausal bleeding occurs with a 10.7% frequency in the general population, 61 is associated with a 4.4% prevalence of endometrial malignancy, 62 and may be an independent predictor of significant endometrial pathology. 59 Although it seems intuitive that the frequency of NECs would be significantly higher in patients presenting with bleeding than in their asymptomatic counterparts, published studies have reported conflicting results on this point (Table 7).…”
Section: Significance Of Associated Symptomsmentioning
confidence: 99%
“…Over 90% of patients with endometrial cancer are postmenopausal and initially present with abnormal vaginal bleeding [1,2]. Ten percent of postmenopausal women will have postmenopausal bleeding [3] and 10% of those will ultimately have endometrial cancer [4]. Sixteen to thirty-five percent of these malignancies will be higher-grade, more aggressive Type 2 endometrial cancers [5].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of vaginal bleeding in postmenopausal women is approximately 10% immediately after menopause and 5% of all cases of menopause [1,2]. Various benign genital causes of postmenopausal vaginal bleeding include atrophic vaginitis, endometrial and cervical polyps, endometrial hyperplasia, pyometra, and submucosal fibroids.…”
Section: Introductionmentioning
confidence: 99%